Construction and application of GOx-based nanoreactor - HUANG Yan (Academic Journals Center of Shanghai Normal University, 2021)
Proteases play an important role in regulating and maintaining the normal function of the living organisms, and are widely used in the diagnosis and treatment of diseases. However, the natural protease is easily deactivated, denatured, and unable to enter cells directly, which greatly limit its application and development. Therefore, it is urgent to construct efficient, safe nanocarriers that can deliver protease into cells. In the present work, a glucose oxidase (GOx)-based nanoreactor was constructed by synthesizing metal-organic zeolite-like nanoparticles with GOx as structural template. The nanoreactor has a high protein loading capacity, and can preserve the catalytic activity of GOx. Cytological experiments indicated that the nanoreactor can effectively enter tumor cells and locate in the lysosomes, consume intracellular glucose, and produce hydrogen peroxide, thus leading to the death of cancer cells. The nanoreactor constructed in this work represents a new safe and efficient platform for intracellular protein delivery.